Exploring the rural passenger experience, information needs and decision making during public transport disruption. (March 2016) - Papangelis, Konstantinos; Velaga, Nagendra R.; Ashmore, Fiona; Sripada, Somayajulu; Nelson, John D.; Beecroft, Mark
Abstract: Individuals in rural areas are often provided with little or no information regarding public transport disruptions. This has strong impact on those with limited access to alternative motorised transport. Though an increasing number of real time passenger information (RTPI) systems are being developed their role in supporting travellers during service disruption is poorly understood, particularly in rural areas. In this paper, we first illustrate and categorise travel disruptions. Requirements for RTPI — particularly for rural public transport users — are then identified for each type and stage of disruption through interviews and focus groups with rural passengers. Patterns of passenger behaviour during travel and transport disruptions are also classified. Further, a conceptual model of the recovery phases of disruption has been developed to map the RTPI requirements for each recovery phase of disruption. The model has been developed and evaluated through a series of focus groups and interviews with passengers, transport service providers, and government agencies. Finally, the paper also discusses and suggests the necessary advances in digital technologies for RTPI systems required to support public transport users during disruptions and thus minimise the number of trips abandoned.